What this comedian said will shock you [compact disc, unabridged] - Maher, Bill (Simon & Schuster Audio, 2024)
Bill Maher revisits more than a decade of editorial segments from his show Real Time on free speech, cops, drugs, race, religion, the generations, cancel culture, and more, rewriting, reimagining, updating them, and adding new material to speak exactly to the moment we're in.